Evaluation of antibacterial activity of Tanzanian gooseberry (Physalis peruviana) leaf extract against multi drug resistance Escherichia coli and Salmonella typhi (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2024)
This study was conducted to evaluate in-vitro antibacterial activities of methanolic leaf extract of P. peruviana growing in Dodoma, Tanzania against multi drug resistant bacteria (Escherichia coli and Salmonella typhi) using two methods, agar well diffusion and standard micro-dilution methods. Moreover, leaf extract was screened qualitatively for the presence of phytoconstituents using standard methods.Methanolic leaf extract of P. peruviana (from 0.2mg/ml to 0.4mg/ml concentrations) showed antibacterial activity against tested E. coli and S. typhi with zone of inhibition (ZOI) ranging from 19 to 21mm and 17.7 to 22mm, respectively. Micro-dilution method revealed the minimum inhibitory concentration (MIC) of methanolic leaf extract of P. peruviana to be 10µg/µl and 5µg/µl against E. coli and S. typhi respectively. Qualitative phytochemical analysis of methanolic leaf extract of P. peruviana identified the presence of tannins, cardiac glycosides, alkaloids, terpenoids and steroid falvonoids and phenols.Methanolic leaf extract of P. peruviana have antibacterial activity against multi drug resistant bacteria (E. coli and S. typhi). This plant can be new sources of future antibiotics that potentially combat the existing problem of antimicrobial resistance.